Quantum mechanical investigation of electronic transport properties of memantine-functionalized gold nanopore DNA nucleobase detector - Kole Abhisek (2017)
The quantum mechanical studies of electronic transport properties of memantine-functionalized gold nanopore biosensor for natural and mutated DNA nucleobase detection are reported. In this study, gold electrode was functionalized with a modified diamondoid structure, called memantine, and the tunneling current arising from the nucleobases was investigated as it translates through the functionalized gold nanopore. Non-Equilibrium Green’s Function (NEGF) and density functional theorem (DFT) methods have been used to analyze and calculate the results. The transmission spectrum for each nucleobase is presented. In order to justify that the resonance peaks are originating from the nucleobases, the Projected Density of States (PDOS) of nucleobases were plotted and compared with their corresponding transmission spectrum. The electronic wave function related to the transmission and the device sensitivity has also been shown. The proposed device is demonstrated to detect various natural and mutated nucleobases with the sensitivity ranging from 103 to 107. Finally, we have investigated the differential conductance for various nucleobases.